Students' Mathematical Communication Skills on Straight-Line Equation Using PMRI and Collaborative Learning - Kristiani, Yasinta Dian; Juandi, Dadang; Putri, Ratu Ilma Indra (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2024)
The study aims to examine students' mathematical communication skills on the material of straight-line equation through video-assisted learning using the Indonesian Realistic Mathematics Education (PMRI) approach and collaborative learning. The type of research is descriptive qualitative research with participants consisting of 20 students in the eighth grade of junior high school in the Palembang District, South Sumatera Province. This study comprised three meetings. The initial two meetings were dedicated to learning process using video material with PMRI and collaborative learning. The third meeting was utilized for result evaluation through testing. Data were collected through written tests, observations, and interviews using the descriptive data analysis approach. The findings of the study reveal that the combination of the PMRI approach, collaborative learning, and video learning on the material of straight-line equation has a fairly effective application. The students’ skills to communicate mathematically are identified. The most frequent indicator is expressing mathematical ideas, while the least frequent indicator is drawing conclusions. Students' mathematical communication skills can be improved by using learning video in conjunction with PMRI and collaborative learning during the learning process.